Uganda : Technical Assistance Report: Report on the Quarterly National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding finalization of the rebased GDP estimates for dissemination. For the economic activity worksheets, the nominal and real growth rates, intermediate consumption/gross output ratios at current and constant prices, and implicit price deflators were checked. A number of adjustments were made to the methodology to improve the representativeness of the indicators and the weights of the composite price indices to ensure the resulting estimates are within expectations. There is considerable scope to improve the price deflators and constant price estimates. Technical Assistance to improve the expenditure estimates will be provided during 2015.